METHODICAL WAYS OF PREPARING A GOALKEEPER TO A HANDBALL GAME (Scientific journal of the Fergana State University, 2023)
As with all sports, the escalation of cross-country competition in handball game and the continuous growth of the result are reinforcing the need to train young talented as well as competitive handball players with great potential. This ultimately requires a special attention to the process of training highly qualified personnel in the sport of handball, as well as the need to revise the mechanism of these systems and form them according to the requirements of the times. This situation imposes a lot of responsible work on the pedagogical — coaches operating in this area, who need to pay special attention to their technical and tactical training in the process of training players in handball sports.This article tried to shed light on the main methods of his technical and tactical training in the preparation of the goalkeeper of the handball game. We think that this in turn will provide practical assistance to improve students ʼ theoretical knowledge to a certain extent.